"For Telling" the Present: Using the Delphi Method to Understand Personal Information Management Practices - Jones, William; Capra, Robert; Diekema, Anne; Teevan, Jaime; Pérez-Quiñones, Manuel; Dinneen, Jesse David; Hemminger, Bradley (CHI 2015, 2015)
Researchers have been studying personal information management (PIM) for many years, but little exists by way of practical advice for how individuals should manage their own information. We employed the Delphi Method to engage PIM researchers with expertise in a variety of relevant areas in a five-round extended dialog about PIM practices. Participants identified key everyday choices of PIM, suggested alternatives, and identified pros and cons of each alternative. Our contributions include: 1) a set of 36 PIM practices, along with pros, cons, and recommendations for or against each practice, 2) directions of future research and development including “near-future” improvements in tool support and 3) a detailed description of how we applied the Delphi Method to study PIM and how it might be used more widely in HCI research as a complement to more established methods of inquiry.